Bilingual language acquisition: The role of input and experience. Issue 1 (30th November 2016) - ABUTALEBI, JUBIN; CLAHSEN, HARALD
Abstract : The question of how much language a child can learn by modelling the patterns she is exposed to in the environment represents an age-old and persistent controversy in language-acquisition research. On a number of occasions researchers felt confident enough to claim that the controversy had been resolved, in favour of their own viewpoint, of course. One such attempt was Skinner's (1957 )behaviourist view of language development, which gave a prominent if not exclusive role to input and experience. After Chomsky's (1959 ) landmark review, however, Skinner's account was left in pieces and was not further pursued by many. A more recent attempt comes fromusage-based accounts according to which children directly build linguistic categories and rules from the language they hear around them. Some believe that these accounts have resolved the controversy for good and have 'overturned' alternative less experience-driven approaches (e.g., Ibbotson & Tomasello, 2016 ; Dabrowska, 2015 ). Yet, casual inspection of recent research articles reveals that this announcement may be somewhat premature; see, for example, Everaert, Huybregts, Chomsky, Berwick and Bolhuis (2015 ), Boxell's (2016 ) rebuttal of Dabrowska (2015 ), and many acquisition studies published in the journal Language Acquisition .